Efficacy of Channa Striata Extract Capsule (Vipalbumin®) for Serum Albumin Level and Wound Healing Postradical Hysterectomy in Cervical Cancer Patients: Efektivitas Konsumsi Kapsul Ekstrak Ikan Gabus terhadap Kadar Albumin Serum dan Penyembuhan Luka Pascahisterektomi Radikal Pasien Kanker Serviks - Chaerannisa Akmelia; Patiyus Agustiansyah; Agustria Z. Saleh; Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: To determine the efficacy of Channa striata extract on serum albumin level and wound healing after radical hysterectomy in cervical cancer patients in Mohammad Hoesin Hospital Palembang.Methods: A clinical trial was conducted in Mohammad Hoesin Hospital Palembang during period of January – September 2019. Samples were cervical cancer patients undergoing radical hysterectomy. Serum albumin level was measured before surgery, after surgery, and after the administration of Channa striata extract capsule. Efficacy of the supplement was analyzed with SPSS version 20 using paired t-test.Result: Twenty-eight cervical cancer patients undergoing radical hysterectomy who fulfilled inclusion criteria were obtained. Majority of patients were aged between 40-49 years old (89.3%), normoweight (39.3%), and lived in rural area. Mean duration of surgery was 154.46 ± 40.47 minutes. Serum albumin level before surgery, after surgery and after the administration of Channa striatus extract were 3.4 ± 0.61 g/dL, 2.91 ± 0.42 g/dL, and 3.11 ± 0.49 g/dL, respectively. There was a statistically significant difference between serum albumin level before and after the surgery (p=0.000). However, no statistically significant difference was found between serum albumin level after surgery and after administration of Channa striata extract capsule (p=0.750).Conclusions: There was no significant difference between serum albumin level after surgery and after administration of Channa striata extract capsule.Keywords: cervical cancer , channa striatus extract , radical hysterectomy, serum albumin level. Abstrak Tujuan: Untuk mengetahui efikasi ekstrak Channa striata terhadap kadar albumin serum dan penyembuhan luka pasca histerektomi radikal pada pasien kanker serviks di RS Mohammad Hoesin Palembang.Metode: Uji klinis dilakukan di RS Mohammad Hoesin Palembang selama periode Januari – September 2019. Sampel adalah pasien kanker serviks yang menjalani histerektomi radikal. Kadar albumin serum diukur sebelum operasi, setelah operasi, dan setelah pemberian kapsul ekstrak Channa striata. Khasiat suplemen dianalisis dengan SPSS versi 20 menggunakan uji-t berpasangan.Hasil: Didapatkan 28 pasien kanker serviks yang menjalani histerektomi radikal yang memenuhi kriteria inklusi. Mayoritas pasien berusia antara 40-49 tahun (89,3%), normoweight (39,3%), dan tinggal di daerah pedesaan. Durasi rata-rata operasi adalah 154,46 ± 40,47 menit. Kadar albumin serum sebelum operasi, setelah operasi dan setelah pemberian ekstrak Channa striatus berturut-turut adalah 3,4 ± 0,61 g/dL, 2,91 ± 0,42 g/dL, dan 3,11 ± 0,49 g/dL. Ada perbedaan yang signifikan secara statistik antara kadar albumin serum sebelum dan sesudah operasi (p=0,000). Namun, tidak ditemukan perbedaan yang signifikan secara statistik antara kadar albumin serum setelah operasi dan setelah pemberian kapsul ekstrak Channa striata (p=0,750).Kesimpulan: Tidak terdapat perbedaan yang bermakna antara kadar albumin serum setelah pembedahan dan setelah pemberian kapsul ekstrak Channa striata.Kata kunci: ekstrak Channa striatus, histerektomi radikal, kadar albumin serum, kanker serviks.